Clothes drying from room air conditioning waste heat: thermodynamics investigation - Mahlia, Teuku Meurah Indra; Hor, C.G.; Masjuki, Haji Hassan; Husnawan, M.; Varman, M.; Mekhilef, Saad (Springer Verlag (Germany), 2010)
This paper discusses an experimental study for using heat wasted from a split-type room air conditioner for clothes drying. The study compares the effectiveness of this drying system to a conventional one in terms of duration required to dry the clothes and energy consumption. The objectives of the study are to analyze performance of a room air-conditioner as clothes dryer and to evaluate the effectiveness of its heat waste for a drying system. The experiment is conducted for three drying conditions, namely, outdoor natural drying at midday, indoor natural drying, and drying using air-conditioner waste heat. The study found that using room air-conditioner waste heat for clothes drying is very reliable, especially in congested high-rise residential areas, without additional electricity cost.